Plant Growth-Promoting Rhizobacteria HN6 Induced the Change and Reorganization of Fusarium Microflora in the Rhizosphere of Banana Seedlings to Construct a Healthy Banana Microflora - Yang, Deyou; Wang, Lanying; Wang, Tianhao; Zhang, Yunfei; Zhang, Shujing; Luo, Yanping (Frontiers in Microbiology, 2021)
Streptomyces aureoverticillatus HN6 was isolated in our previous study and effectively controlled banana Fusarium wilt. We explored the role of HN6 in constructing a healthy rhizosphere microflora of banana seedlings. The method of antibiotic resistance was used to determine the colonization ability of HN6. The effect of HN6 on the rhizosphere microbial communities was assessed using culture-dependent and high-throughput sequencing. The effect of HN6 on the infection process of the pathogen was evaluated using a pot experiment and confocal laser scanning microscopy. The results showed that HN6 could prevent pathogen infection; it increased the nutrient content and diversity of the bacterial community in the rhizosphere, promoted plant growth, and decreased the mycotoxin fusaric acid content and abundance of pathogens in the banana rhizosphere. Thus, HN6 decreased the relative abundance of Fusarium species, increased the diversity of fungi, and increased the relative abundance of bacteria in the rhizosphere. HN6 induced the change and reorganization of the microbial community dominated by Fusarium in the rhizosphere of banana seedlings, and it evolved into a community dominated that was not conducive to the occurrence of diseases, shaping the rhizosphere microflora and promoting the growth of banana.